Optimization of the Use of Input in Turmeric Farming in Ibru Village, Mestong District, Muaro District, Jambi - Damayanti, Yusma; Nurchaini, Dewi Sri; Ulma, Riri Oktari (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
This research was conducted in Ibru Village, Mestong District, Muaro Jambi Regency, focusing on turmeric farmers as respondents. The study aimed to achieve three primary objectives: (1) to analyze the production function associated with turmeric farming, (2) to evaluate the level of optimization and economic efficiency in the utilization of production factors, and (3) to determine the optimal use of production inputs in turmeric cultivation. A census approach was employed, encompassing all 26 turmeric farmers in Ibru Village as the study’s respondents. The methodological framework utilized the Cobb-Douglas production function analysis, followed by optimization calculations to assess economic efficiency. The results of the study indicated several key findings: (1) land and labor inputs were found to significantly impact the increase in turmeric production per hectare annually, while the inputs of seeds and compost fertilizers did not show a significant effect on production levels; (2) the current use of land and labor in turmeric farming was identified as economically inefficient; and (3) optimization analysis suggested that there is potential for expanding turmeric farming to 1,925 hectares, with a corresponding increase in labor utilization to 31,213 labor days (HOK). These findings provide valuable insights into the efficiency of production practices in turmeric farming and offer guidance for potential improvements and expansion in the sector.